The bean method as a tool to measure sensitive behavior. Issue 2 (21st December 2020) - Jones, Sorrel; Papworth, Sarah; Keane, Aidan M.; Vickery, Juliet; St John, Freya A. V.
Abstract: Conservationists need to measure human behavior to guide decisions and evaluate their impact. However, activities can be misreported and reporting accuracy may change following conservation interventions, making it hard to verify any apparent changes. Techniques for asking sensitive questions are increasingly integrated into survey designs to improve data quality, but some can be costly or hard for nonexperts to implement. We demonstrate a straightforward, low‐cost approach, the bean method in which respondents give anonymous answers by adding a colored bean to a jar to denote a yes or no response. We applied the bean method to measure wild‐meat hunting and trading over 2 years at a conservation‐project (hunting reduction) site in Gola Forest, Liberia. We extended the technique to accommodate questions about hunting and meat‐selling frequency. We compared responses given using the bean method and direct questioning for groups that did and did not participate in conservation interventions. Results from the bean method corresponded to those from direct questioning, and there was no indication of change in question sensitivity following conservation interventions. Estimates from both methods indicated that wild‐meat trading decreased in project and nonproject households (from 36% to 20%) and that hunting decreased in 1 project group (38–28%). Where inconsistent answers were given (2–6% of respondents), differences were in both directions and were most likely attributable to measurement error. The bean method was quick and straightforward to administer in a low‐literacy setting. We showed how it can be modified for answers of more than 2 categories and consider it a valuable tool that could be adapted for a wide range of conservation settings. Abstract : El Método del Frijol como Herramienta para Medir los Comportamientos Sensibles Resumen: Los conservacionistas necesitan medir el comportamiento humano para dirigir las decisiones tomadas y evaluar su impacto. Sin embargo, las actividades pueden estar mal reportadas y la fiabilidad de los reportes puede cambiar después de implementadas las intervenciones de conservación, lo cual complica la verificación de cualquier cambio aparente. Las técnicas para realizar preguntas sensibles cada vez se integran más al diseño de los censos y así mejorar la calidad de los datos, aunque algunas pueden ser caras o complicadas de implementar para quienes no son expertos. Demostramos una estrategia directa y de bajo costo, el método del frijol, en el cual los respondientes proporcionan respuestas anónimas al añadir un frijol pintado dentro de un frasco y así indicar una respuesta de sí o no. Aplicamos el método del frijol para medir la cacería y el mercado de carne silvestre durante dos años dentro de un proyecto de conservación (reducción de la cacería) en el bosque Gola, Liberia. Extendimos la técnica para acomodar preguntas sobre la frecuencia de la caza y la venta de carne. Comparamos las respuestas dadas usando el método del frijol y aquellas dadas en el cuestionamiento directo a grupos que participaban o no en las intervenciones de conservación. Los resultados obtenidos con el método del frijol correspondieron a aquellos obtenidos con los cuestionamientos directos y no hubo indicación de cambios en la sensibilidad de las preguntas después de las intervenciones de conservación. Las estimaciones de ambos métodos indicaron que el mercado de carne silvestre disminuyó en los hogares participantes o no en el proyecto (de 36% a 20%) y que la cacería disminuyó en un grupo del proyecto (38% a 28%). En donde se dieron respuestas contradictorias (2‐6% de los respondientes), las diferencias fueron en ambas direcciones y en su mayoría probablemente eran atribuibles al error en la medición. El método del frijol fue rápido y directo para administrarlo en un ambiente de bajo alfabetismo. Mostramos cómo puede modificarse para respuestas con más de dos categorías y lo consideramos una herramienta valiosa que podría adaptarse para una gama amplia de escenarios de conservación. 摘要: 保护主义者常常需要测量人类行为来指导决策及评估其影响。然而, 对人类行为的报告可能存在问题, 且报告的准确性可能会随着保护措施变化而变化, 以致难以确定明显的变化。设计调查时已越来越多地纳入了询问敏感问题的技巧, 以提高数据质量, 但对于非专业人士来说, 有些技巧可能成本过高或难以实现。本研究展示了一种简单、低成本的方法——bean方法, 在使用该方法时, 受访者只需向罐子中放入一个彩色的豆子 (bean) 来匿名地回答"是"或"否"。我们在利比里亚戈拉森林利用该方法调查了一个保护项目 (减少狩猎) 中人们对野味狩猎和交易的态度。我们通过扩展相应的方法, 将其应用于狩猎和野味交易频率的提问中, 并在曾经参与和没有参与保护干预的群体中, 比较了使用 bean 方法和直接询问获得的回答。使用 bean 方法的结果与直接询问的结果相互一致, 且在进行保护干预后, 问题敏感性没有明显变化。两种方法的估计结果均表明, 有无参与保护项目的家庭的野味交易都有所下降 (从 36% 减少到 20%), 另外, 保护项目的一个参与组还减少了狩猎 (从 38% 减少到 28%) 。当受访者给出不一致的答案时 (占受访者 2–6%), 差异存在于两个方向, 这最有可能是来自测量误差。 bean 方法在受访者的低文化水平背景下有助于快速而直接的实施调查。我们还展示了当答案超过两种类型时如何调整该方法。最后, 我们认为 bean 方法作为一项保护工具很有价值, 可以广泛适用于不同背景下的保护。【翻译: 胡怡思;审校: 聂永刚】